2012
DOI: 10.1159/000342071
|View full text |Cite
|
Sign up to set email alerts
|

‘Bovine’ Aortic Arch – A Marker for Thoracic Aortic Disease

Abstract: Objectives: Very few studies have addressed the clinical significance of ‘bovine’ aortic arch (BA). We sought to determine whether BA is associated with thoracic aortic disease, including thoracic aortic aneurysm, aortic dissection, aortic rupture, and accelerated aortic growth rate. Methods: We retrospectively reviewed CT and/or MRI scans of 612 patients with thoracic aortic disease and 844 patients without thoracic aortic disease to determine BA prevalence. In patients with thoracic aortic disease, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 35 publications
(19 reference statements)
2
75
2
Order By: Relevance
“…More recently, a link between bovine aortic arch anatomy and thoracic aortic aneurysms has also been suggested [9]. In the majority of patients (74%), there are three great vessels branching from the aortic arch: the innominate artery, the left carotid artery, and the left subclavian artery [10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a link between bovine aortic arch anatomy and thoracic aortic aneurysms has also been suggested [9]. In the majority of patients (74%), there are three great vessels branching from the aortic arch: the innominate artery, the left carotid artery, and the left subclavian artery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with concomitant bicuspid aortic valve (BAV) and bovine aortic arch (BAA) were studied specifically to gain a better understanding of why these patients may be more susceptible to AsAA and dissection (10,14,42). BAV and BAA are common congenital malformations of the aortic anatomy.…”
mentioning
confidence: 99%
“…In this issue of Cardiology, Hornick et al [7] suggest that the bovine aortic arch may be a ‘marker of thoracic aortic disease’. The authors retrospectively analyzed chest computed tomography and magnetic resonance imaging studies in 612 patients who were evaluated at the Aortic Institute at Yale-New Haven Hospital, New Haven, Conn., USA, between 2003 and 2010.…”
mentioning
confidence: 99%
“…The authors suggested that focal aortic fragility possibly related to abnormal hemodynamics in the bovine aortic arch was responsible for these findings. Hornick et al [7] demonstrated a higher aortic growth rate in the descending thoracic aorta in patients with aortic disease and a bovine aortic arch. The precise underlying molecular-pathophysiologic mechanism for these abnormalities remained to be defined.…”
mentioning
confidence: 99%